2015
DOI: 10.7874/jao.2015.19.3.132
|View full text |Cite
|
Sign up to set email alerts
|

Positive, Neutral, and Negative Connotations Associated with Social Representation of 'Hearing Loss' and 'Hearing Aids'

Abstract: Background and ObjectivesIn our previous studies we explored the social representation of hearing loss and hearing aids. In this study we aimed at exploring if the positive, neutral and negative connotations associated with the social representation of 'hearing loss' and 'hearing aids' for the same categories vary across countries. In addition, we also looked at if there is an association between connotations and demographic variables.Subjects and MethodsA total of 404 individuals from four countries were aske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…It is also clear that pure-tone audiometry has limitations in regard to determination of hearing difficulty 21 and other outcomes of subjective hearing status are important to determining influence on communication and quality of life. 22,23 Finally, there is also a negative social connotation associated with hearing loss that may lead some to disregard or continue to believe their hearing is good. 20,21…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also clear that pure-tone audiometry has limitations in regard to determination of hearing difficulty 21 and other outcomes of subjective hearing status are important to determining influence on communication and quality of life. 22,23 Finally, there is also a negative social connotation associated with hearing loss that may lead some to disregard or continue to believe their hearing is good. 20,21…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hearing loss is painless and invisible, therefore it is not always recognized by primary care physicians and, if not brought into the patient-physician dialogue, may further reinforce lack of awareness and delay referral for an audiological evaluation. It is also clear that pure-tone audiometry has limitations in regard to determination of hearing difficulty and other outcomes of subjective hearing status are important to determining influence on communication and quality of life . Finally, there is also a negative social connotation associated with hearing loss that may lead some to disregard or continue to believe their hearing is good …”
Section: Discussionmentioning
confidence: 99%
“…Deaf and hard of hearing (DHH) people, including those with PD, constantly feel a strain in everyday life, giving rise to tension, stress, uncertainty, or fatigue [ 17 ]. This often leads to stigma, so the social context of DHH people should not be overlooked [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also interesting that an intercultural comparison of the hearing aid acceptance in different countries revealed that the social acceptance of hearing aids is different in different cultures. The study compared the specific situations in India, Iran, Portugal, and England [ 82 ], [ 83 ].…”
Section: Necessity Of Early Hearing Rehabilitation and Hearing Aidmentioning
confidence: 99%